Capital flows to Emerging Markets: Liberalization, Overshooting, and Volatility - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 1998)
The paper analyses the impact of financial liberalization and reform in emerging markets on the dynamics of capital flows to these markets, using a simple model of international investors' behaviour. We first show that the gradual nature of liberalization, combined with the cost of absorbing large inflows in emerging eonomies, leads to rich dynamics of capital flows and often implies an initial period of overshooting as portfolios adjust. Asset prices will also overshoot. Second, we show that, if investors have incomplete information about new emerging markets, and learn over time, there can be high volatility of capital flows and contagion. Finally, we provide numerical estimates of long-run capital inflows to emerging market economies and compare them to actual inflows. This gives a good indicator of upcoming crisis situations.
Keywords: F21; F32; 330; Kapitalmobilität; Finanzmarktregulierung; Schwellenländer; Volatilität; Unvollkommene Information; Lernprozess; Theorie